THE EDUCATIONAL REINTEGRATION OF THE REMIGRANT PUPILS IN ROMANIAN SCHOOLS. CASE STUDY IN VRANCEA COUNTY - Florentina CIOMAGA (National Centre for Policy and Evaluation in Education, 2019)
The educational system in Romania is facing the new challenge of reintegrating the children that returned in their home country after a period of migration, and the update in the educational procedures is becoming more and more important as the number of the remigrant children is rapidly increasing, the most recent estimations mentioning 150,000-180,000 (Brebuleţ, 2018). This research investigated the social perception of the remigrant pupils in the educational field (native pupils and teachers) and the potential changes that teachers, schools and the system could implement (from specific activities to institutional update and development of new didactic instruments). The research methodology was quantitative, based on a questionnaire with Likert type scales. Previous researches in Vrancea county showed the psychological, social and educational effects of remigration, but the updates in the educational system to better respond those needs is more dependent on their perception by the decision makers (teachers and school management) and by the native children. Ideally, the social perception should adequately reflect the educational reality. Still, what happens if the perception of the native children and teachers does not reflect reality? What happens if the majority of children could not identify the problems the remigrants face after returning to Romania? What if the teachers, when planning, implementing and evaluating the educational activities, don't rely on an adequate knowledge of the difficulties that remigrants have to face, can they support the educational system to better respond to the specific needs of the remigrants?